The effect of ball carrying on the sprinting speed of international rugby union players - Barr, M. J.; Sheppard, J. M.; Gabbett, T. J.; Newton, R. U. (International Journal of Sports Science and Coaching, 2015)
Speed is considered to be a highly valuable ability in rugby union. One unique aspect of rugby is that players need to be effective at sprinting while carrying a rugby ball. Previous research reported that amateur club players were slower while sprinting with the ball, than without. The purpose of the current research was to examine how sprinting while carrying a ball affected the sprinting speed of international rugby players. Twenty-six international players performed 6 x 40 m sprints under three conditions: Ball One Hand (B1H), Ball Two Hands (B2H) and No Ball (NB). Timing gates were placed at the 0 m, 10 m, 30 m and the 40m mark of the sprint. The 0-10m was used to examine initial acceleration; 30-40 m was used to examine maximal velocity and the 10-30 m section to analyze the acceleration up to maximal velocity. Comparisons were also made between backs and forwards. Backs were found to be faster than forwards at each of the splits for the NB, B1H and B2H conditions (0.04 - 0.08 s, p<0.0001 - p=0.015, d=0.88 - 1.35). The results of the study showed only trivial and small differences (1-2%) between the B1H and B2H conditions with the NB condition. The decrements in speed from the B2H conditions were much less for the international players when compared with previously reported data from amateur club players. Coaches working with rugby players should regularly incorporate sessions focused on speed development, as well as including B1H and B2H as part of a speed testing battery.